EARNING PER SHARE, PRICE EARNING RATIO, PRICE BOOK VALUE, NET PROFIT MARGIN, TOTAL ASSET TURNOVER, DAN HARGA SAHAM - Juliani, Indah; NurLaela, Siti; Masitoh, Endang (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2021)
Abstac Stock investment is one investment that has attracted the interest of many people. Although there are risks because the stock is very sensitive to changes that can have an impact on stock prices. But stock investments offer high returns and opportunities. The purpose of this study was to determine and analyze the effect of Earning Per Share, Price Earning Ratio, Price Book Value, Net Profit Margin, and Total Asset Turnover on stock prices. The population of this study is the chemical and pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange in 2012-2018. The number of samples of this study were 8 companies, with sampling using a purposive sampling method that is sampling based on certain criteria. The analysis technique uses multiple linear regression with the results showing that Earning Per Share, Price Earning Ratio, Price Book Value, and Net Profit Margin affect the stock price. While Total Asset Turnover has no effect on stock prices. Keyword : Earning Per Share, Price Earning Ratio, Price Book Value, Net Profit Margin, Total Asset Turnover, Stock Price